John Milton : life, work, and thought - Campbell, Gordon; Corns, Thomas N. (Oxford scholarship online, 2023)
This biography of Milton is based on 40 years of original research, and takes account of new thinking about 17th-century England. He is seen here as flawed, passionate, ruthless, and ambitious, as well as one of the most accomplished writers of the time and author of the most influential narrative poem in English.
Keywords: Milton, John, : 1608-1674; Poets, English : Early modern, 1500-1700 : Biography; Biography; Great Britain : History : Stuarts, 1603-1714